Board Gender Diversity and IPO Price Formation in Indonesia - Vivi Liu; Sung Suk Kim (Universitas Pelita Harapan, 2025)
This study aims to analyze the effect of gender diversity in boards of commissioners and directors on the level of underpricing on the first trading day following an Initial Public Offering (IPO) in Indonesia. The data used consist of companies that conducted IPOs in Indonesia dure in Indonesia during the period 2021-2024. The results indicate that in the Indonesian market, investors place greater emphasis on firms’ fundamental factors rather than gender-related aspects when making investment decisions at the time of an IPO. Market Capitalization, Return on Assets (ROA), and Share Overhang (SO) are found to be significant variables. This study contributes to the literature on factors influencing stock market performance during IPOs and provides practical implications for firms and regulators in formulating IPO strategies. Future research could be extended by incorporating additional factors such as financial characteristics, macroeconomic conditions, and managerial aspects in shaping investor decision-making.